Esoterisme Apolitis Islam Syiah Imamiyah: Pengantar dan Terjemah atas Comments on the “Political” Life of the Imams Karya Muhammad Ali Amir-Moezzi - Asri, Syamsul (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
There is an idee fixed that Twelver Shia Islam, or Imami Shia, is an Islamic school whose primary doctrinal character is political, subversive, and revolutionary. Revolving around the doctrines of Imamah/Leadership and `Adalah/Justice and framed in its modern manifestations in Lebanon, Iran, Iraq, and Yemen, this idee fixed is prevalent as scientific truth. This paper aims to compete with, or at least complement, the dominant view in Shia studies. Rather than being read as a set of political doctrines and movements, Imami Shia Islam, with the figure of the Imam as the Divine Guide in its central position, is an apolitical religion par excellence. This paper continues by positioning the moment of Occultation of the Twelfth Imam as the most impactful historical moment in the history of Imami Shia, which transformed the character of doctrine from its initially esoteric, non-rational nature to a rational-juridical one. Following the methodology developed by Muhammad Ali Amir-Moezzi, this paper argues against the poverty of political interpretations of the figure of the Imam and proposes a return to the study of Imami Shi'ism as the most archaic form of Islamic esotericism. This methodological position is more in line with the earliest source texts produced during the life of the Imami Shi'i figures, up to the period of the Minor Occultation. The final section of this paper presents the very first translation into Indonesian Language of a sub-chapter entitled "Comments on the "Political" Life of the Imams" from Muhammad Ali Amir-Moezzi's book, The Divine Guide in Early Shi'ism: The Source of Esotericism in Islam. This text was chosen because it contains key arguments regarding the relationship of Imami Shi'i imams to the political life of their time, and how Imami Shi'i Islam cannot be reduced to mere political positions.